Optimization of the intron sequences combined with the CMV promoter increases recombinant protein expression in CHO cells - Ting-Ting Xu; Yan-Fang Wang; Jing-Jia Yuan; Chun-Liu Mi; Shao-Lei Geng; Xiao-yin Wang; Tian-Yun Wang (Scientific Reports)
Abstract To meet the requirements of the biopharmaceutical industry, improving the yield of recombination therapeutic protein (RTP) from Chinese hamster ovary (CHO) cells is necessary. The human cytomegalovirus (CMV) promoter is widely used for RTP expression in CHO cells. To further improve RTP production, we truncated the human CMV intron and further evaluated the effect of four synthetic introns, including ctEF-1α first, EF-1α first, chimeric, and β-globin introns combined with the CMV promoter on recombinant expression levels in transient and stably recombinant CHO cells. The results showed that the truncated, EF-1α first, chimeric, and β-globin introns can significantly improve stable transgene expression in CHO cells. The qPCR results indicated that the mRNA level of transgene increased through optimizing intron sequences combined with the CMV promoter. Transcriptomics analysis was performed and found that differential expression of genes involved in mRNA processing, RNA export from nucleus, cytoplasmic translation, transcriptional activation and cell cycle regulation. In conclusion, optimization of the intron sequences combined with the CMV promoter can achieve a higher yield of recombinant proteins in CHO cells. This will be valuable for generating CHO cell lines with high productivity for industrial applications.